Analysis and Design of a School Information System to Improve the Quality of Education at RA Al-Hida - Widayani, Hapsari; Fahrudin, Ahmad (NUCLEUS, 2025)
The purpose of this research is to create an integrated web-based computerized system, providing knowledge for understanding digital literacy to teachers and parents of students so that RA Al-Hida school can progress, increase the number of students, build adequate digital infrastructure, and of course can improve the quality of education. This research uses observation, interview, and survey methods to identify system needs. System development in this research applies the System Development Life Cycle (SDLC) model which includes the stages of planning, analysis, design, development, implementation, and testing. Testing was conducted for seven days using a questionnaire instrument of 15 items to 4 teachers and 6 parents of students. The results of the study indicate that the developed system is able to meet the operational needs of the school. The average value of user assessment is above 4.5 in the aspects of ease of access, access speed, suitability of features, and readiness of digital infrastructure. The implementation of the system also has a positive impact on increasing the number of new students, namely from 18 students in 2024 to 29 students in 2025. In addition, the system helps improve administrative effectiveness, data accuracy, and communication between teachers and parents. This study concludes that the implementation of web-based SIMS and LMS is able to address the main problems at RA Al-Hida, strengthen users' digital literacy, and support the improvement of the quality of educational services through the use of technology that is easily accessible, structured, and relevant to the school's needs.